Kevalidan LKPD Berorientasi Model Problem Based Learning Materi Gaya Kelas IV SDN 24 Pontianak Tenggara - Karwadi, Tamara; Kartono, Kartono; Pranata, Rio (Pendidikan Islam Anak Usia Dini STIT Palapa Nusantara, 2024)
This research and development aims to produce a Problem-Based Learning (PBL) model-oriented Student Worksheet (LKPD) product for the Science and Social Studies (IPAS) subject, specifically focusing on the topic of the influence of forces on objects for fourth-grade elementary school students. The objective is to create a valid and suitable tool to assist the learning process within the Independent Learning Curriculum. The method employed is the research and development (R&D) approach, adapting the ADDIE model and modifying it into ADD. The research sample consists of 2 validators and 24 students. Data collection techniques include questionnaires and interviews. The results of the research and development received feasibility assessments from 2 validators, with an average score of 4 for the didactic aspect, categorized as